Konstruksi Filsafat Pendidikan di Pondok Pesantren Ali Muttaqin Ponorogo - Rizqi, M. Rizal (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2023)
This study aims to describe the philosophy of education at the Ali Muttaqin Islamic boarding school, Ponorogo. Islamic boarding schools are the oldest Islamic educational institutions in Indonesia. In its development, Islamic boarding schools are influenced by educational developments and dynamic community needs, several Islamic boarding schools organize (formal) school education and other activities aimed at increasing the economic potential of the surrounding community by establishing Islamic boarding schools as the center. In the implementation of education, Islamic boarding schools are based on the foundation of educational philosophy. The model used in this study is a field study, namely going directly to the field to explore Islamic philosophical issues at the khalaf Islamic boarding school. The method used in this research is qualitative method. This method is defined by obtaining research data by conducting interviews, observations, and documentation studies. Observations were made directly at the Ali Muttaqin boarding school. This research produced three findings, namely: (1) the ontology foundation of educational philosophy at the Ali Muttaqin boarding school. (2) the epistemological basis of educational philosophy at the Ali Muttaqin boarding school. (3) The axiological foundation of educational philosophy at the Ali Muttaqin boarding school.